Neuroimaging and Reading Comprehension - Perkins, Kyle; Jiang, Xuan (Journal of Interdisciplinary Studies in Education, 2019)
In this position paper, we advocate that advancements made in other disciplinary areas such as neurolinguistics should be included into contemporary reading comprehension courses and programs. We present findings from neurobiology of reading that suggest explanation of certain reading behaviors: (1) the differences between reading disability and typically developing readers; (2) an inverted U-shaped function that reflects the fact that learning to read is associated with increased activation (the rising part of the inverted U) and activation decreases are associated with familiarity, experience, and expertise (the falling part of the inverted U); (3) and, the identification of reading networks. As potential pedagogical implications of neuroimaging studies to reading, a list of sentence structures is proposed as an example to further relate reading comprehension to cognitive capacity limits.